2016
DOI: 10.1093/annonc/mdv610
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor-infiltrating lymphocytes in Epstein–Barr virus-associated gastric cancer

Abstract: The histologic subclassification and TILs can be used to predict RFS and DFS for patients with EBVaGC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 29 publications
7
116
0
2
Order By: Relevance
“…This demonstrates that immune escape mechanism mediated by PD-1 may play an even broader and crucial role in EBV+GC. Furthermore, some previous study demonstrated that more TILs were present in EBV+ GC [41][42][43]. And patients with the lymphoepithelioma-like carcinoma (LELC) subtype had better OS and DFS than patients with the other subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that immune escape mechanism mediated by PD-1 may play an even broader and crucial role in EBV+GC. Furthermore, some previous study demonstrated that more TILs were present in EBV+ GC [41][42][43]. And patients with the lymphoepithelioma-like carcinoma (LELC) subtype had better OS and DFS than patients with the other subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumorigenic properties of immune cells (T-, as well as B-lymphocytes) are well-established and high levels of TILs are commonly associated with improved survival in a variety of tumors, including gastric carcinomas (2,23).…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al [90] assessed the prognostic value of TILs amongst EBV-associated gastric carcinomas using a modification of the International Immuno-Oncology Biomarkers Working Group guidelines for breast carcinoma [1]. sTILs were found to be an independent prognostic factor for recurrence free survival but not overall survival, while iTILs were not significantly associated with either recurrence free or overall survival [90]. Giamperi et al used a similar approach and found that sTILs were significantly associated with dMMR status, but that both sTILs and dMMR status were independent favorable prognostic factors in a multivariate model [91].…”
Section: Tils In Upper Gastrointestinal Tract Carcinomasmentioning
confidence: 99%